2005
DOI: 10.3184/095422905782774937
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus release in response to pH variation in the lake sedimentswith different ratios of iron-bound P to calcium-bound P

Abstract: (2005) Phosphorus release in response to pH variation in the lake sedimentswith different ratios of iron-bound P to calcium-bound P, Chemical Speciation & Bioavailability, 17:2,[55][56][57][58][59][60][61] ABSTRACTPhosphorus released from the sediment may render lakes eutrophic under appropriate pH and redox conditions. Phosphorus speciation in lake sediments was investigated by a Standard Measurements and Testing (SMT) protocol in three shallow lakes: Taihu Lake, Chaohu Lake and Longganhu Lake in the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…Desorption and flush‐out of labile P with ambient stream water offer another explanation for the smaller proportion of labile P in the bed sediment (Dorioz et al, 1989; Reddy et al, 1999). Especially eroded particles from acidic soil will lose labile and moderately labile Pi via desorption because of an increase in pH to slightly alkaline by the stream water (Ammer water: pH 7.3–8.1; Supplemental Table S4) (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Desorption and flush‐out of labile P with ambient stream water offer another explanation for the smaller proportion of labile P in the bed sediment (Dorioz et al, 1989; Reddy et al, 1999). Especially eroded particles from acidic soil will lose labile and moderately labile Pi via desorption because of an increase in pH to slightly alkaline by the stream water (Ammer water: pH 7.3–8.1; Supplemental Table S4) (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Jensen, Kristensen, Jeppesen and Skytthe [23] analyzed sediment from 12 different lakes and found that for aerobic sediments the phosphate concentration is related to the Fe:P ratio and total iron controls the maximum adsorption capacity [25]. Phosphorous releases are also affected by calcium concentrations with release rates more affected by pH than redox conditions [26].…”
Section: Phosphorus Release From Sedimentsmentioning
confidence: 99%
“…After determination, the sediment background values are NaOH-P 57.76 mg/kg, HCl-P 6.01 mg/kg, IP 63.77 mg/kg, Or-P 12.73 mg/kg and TP 76.49 mg/kg, accounted for the 75.51%, 7.86%, 83.37%, 16.63% and 100% of TP respectively. It is clear that the sediments are mainly composed by inorganic phosphorus, and the inorganic phosphorus mainly contains NaOH-P component, suggesting that the agricultural water body pollution is serious [15].…”
Section: Sedimentsmentioning
confidence: 99%